Pengembangan Sistem Pengukuran Gaya Tumbukan pada Jurus Pukulan Datar Pencak Silat Menggunakan Sistem Strain Gauge - Muhammad Rizal; Iskandar Hasanuddin; Muhammad Asyraf (Jurnal Teknik Mesin Unsyiah, 2019)
Force plate is a tool that is very useful for knowing the amount of force produced by an athlete. This tool can help trainers or sports researchers in the physical development of an athlete. This research is a development of a tool for measuring the force that calculates collision forces while assessing the characteristics of a strain gauge-based transducer for flat punch moves from Pencak Silat. The analysis was done theoretically to determine the characteristics of this measuring instrument and experimentally to figure out the validation of the measuring instrument. This impact force measurement instrument has been made and can absorb about 2000N. It has sensitivity about 0.0981 mV/N, has linearity deviation about 1.169 mV (9,431), and has hysterisis percentation about 5,3%. The result of validation test that has it biggest deviation about 2.99 N. Thus, this tool can be used to measure the impact force which was produced from the Pencak Silat flat punch moves.